Pengaruh Fraksi Volume Serat Dengan Matriks Epoxy Pada Material Komposit Serat Mendong - Gugun Gundara; Dikri Saepul Robani; Aceng Sambas (PT FORMOSA CENDEKIA GLOBAL, 2022)
A composite material is a material that is a mixture of two or more macroscopically mixed materials, so the properties of its forming material are still clearly visible. In this study, the type of fiber used was the natural fiber of mendong. This mendong fiber is made into a composite material using the Hand Lay-up method with four variations in fiber volume, namely (30%, 40%, 50%, and 60%). The fiber binding material (matrix) used is Epoxy. This study aims to determine the characteristics of jack fibers in jack fiber composite materials with an epoxy matrix against tensile strength and modulus etalciticity. Tensile testing refers to the ASTM D 638 Standard. To find out the type of fault from the tensile test results, macro photos are used and find out the shape of the fault and the failure pattern that occurs in composite specimens. From the test results, it is clear that the difference in the composite material of mendong fiber using Epoxy, that with a fiber volume fraction of 60% greater mechanical properties